Créditos - FALE - UFMG, Pós-Lit (Em Tese, 2014)
EDITORES EM TESECleber Araújo CabralFelipe Oliveira de PaulaGustavo Cerqueira GuimarãesJoão Alves Rocha NetoJosué Borges de Araújo GodinhoJulia Gomes PanadésRafael Otávio Fares